Correlates of egg size variation in a population of house sparrow Passer domesticus - Kvalnes, Thomas; Ringsby, Thor Harald; Jensen, Henrik; Sæther, Bernt-Erik (Oecologia, 2013)
Propagule size represents an important life-history trait under maternal control. Despite a positive relationship between propagule size and components of fitness, propagule size displays tremendous amounts of variation which causes are poorly understood within natural populations. With a study of a house sparrows Passer domesticus, we investigate maternal and environmental correlates of egg size, quantify variation in egg size within and between females and broods, and estimate heritability. Egg size had a curvilinear relationship with clutch size and decreased significantly in subsequent broods within seasons. Furthermore, egg size increased with maternal body mass, was positively affected by spring temperatures and curvilinearly related to temperature during the 2 weeks prior to egg laying. Some 46.4 % of variation in egg size was due to differences between females, and 21.9 % was explained by variation between broods by the same female. The heritability of egg size was low (h 2 = 0.26) compared to estimates from other studies (h 2 > 0.6). The present study challenges the recent idea that egg size is an inflexible maternal characteristic with very high additive genetic variance, and suggests that females are subject to both intrinsic and extrinsic constraints prior to and during egg formation, leading to the observed plasticity in egg size. In a general sense, propagule size could be expected to be both limited by and adaptively adjusted in accordance to prevailing environmental conditions.